Mapping Digital Financial Management in Developed and Developing Countries through Bibliometric Analysis - Muhammad Ijlal Siraj Muyassar; Erwin Budianto; Muhamad Wildan Maulana; Adi Setiawan (SEULANGA SYSTEM PUBLISHER, 2025)
Digital financial management has become an important pillar of global economic progress, transforming the way individuals, businesses and countries manage finances. In developed countries, digital banking and payment systems are rapidly evolving, while in developing countries, the adoption of digital technologies continues to increase, as seen by the widespread access to fintech and mobile banking services. Since 2017, research on technology in financial management has shown an upward trend, with bibliometric analysis used to map trends, challenges and influencing factors across different countries. The early 2000s were a pivotal moment in the evolution of digital financial management, driven by the use of smartphones as the primary access to the internet. Research from 1706 to 2025 recorded exponential growth, especially since 2014. Researchers utilise platforms such as Google Scholar to disseminate information widely. Keywords such as “Fintech,” “big data,” and “digital finance” indicate further research opportunities. Fintech has revolutionised financial services with technologies such as blockchain and big data, increasing efficiency, transparency, and personalisation of services, and driving innovation in the global financial ecosystem.